Elizabeth Bennet: a woman of her time - Deon Rossato, Bianca (Cadernos do IL, 2016)
This article analysis the composition of the characters Elizabeth Bennet, from Pride and Prejudice (1813), by Jane Austen, and Lizzie Bennet, from The Lizzie Bennet Diaries (2012-2013), a video blog series aired on YouTube by Hank Green and Bernie Su. Its aims at observing how human relationships are constructed so it is necessary to observe elements of both protagonist’s social contexts, which involve mainly women’s position in society. In order to that, the theories of Vivien Jones (2012), Robert Miles (2013) and Angela McRobbie (2009) are essential. Observing both protagonists’ contexts one can affirm that they emulate the dilemmas of women of their time and, in portraying such strong human relationships, attract many fans, scholars and theorists to their realm.